Sífilis e pré-natal: conhecimento e prática dos profissionais das Estratégias de Saúde da Família do município de Campo Grande-MS - Ramos, Iara Barbosa (2022)
Gestational syphilis is a sexually transmitted infection, easily and quickly diagnosed, considering access to Rapid Tests is still considered a serious public health problem in the world and in Brazil, due to the risk of vertical transmission, which if not treated in a timely manner, can pose risks to both the baby and the pregnant woman. Routine prenatal consultations available in the Unified Health System through the Family Health Units, if carried out following ministerial protocols, offer an active search for infection, in the first and third trimester of pregnancy and if serological reagent is found, early treatment should be a priority. OBJECTIVES: To describe the knowledge and practices of professionals who perform prenatal care in family health strategies in the city of Campo Grande - MS, in relation to gestational syphilis. METHODOLOGY: This is a cross-sectional, descriptive, exploratory study with a quantitative approach. The study was carried out in the municipality of Campo Grande, capital of the state of Mato Grosso do Sul. Participated in the study, nurses and doctors who perform prenatal consultations, working in the Family Health Strategies (ESF) of Campo Grande - MS, during the data collection period, who consented to participate in the research and who met the inclusion criteria . RESULTS: Most participants (43.6%) had no specialization, had correct knowledge about how syphilis is transmitted during pregnancy, as well as correct information about the trimester of pregnancy in which the examination is requested and the recommended treatment. for a pregnant woman with a diagnosis of syphilis of unknown duration, but only 47.3% of the professionals correctly answered the recommended treatment for a pregnant woman with a diagnosis of primary syphilis. CONCLUSION: With regard to prenatal care, the delay in diagnosis, the difficulty in accessing exams or even late exams linked to insufficient knowledge of the classification and the decision of the correct treatment, reinforce the possible gaps in screening and diagnosis, which would enable early diagnosis and treatment. We must also consider the stigma of STIs, as well as Syphilis, to exist, so the approach to the sexuality of health users, the risks and weaknesses in which they may be inserted, the difficulty in understanding the guidelines often technical results in alienating the real user in favor of the “ideal” user, not directing the guidelines and preventions in the face of real specific and individual needs